Unraveling the functional landscape of ATRA- and DMSO-differentiated HL-60 cells - Susanna Ghonyan; David Poghosyan; Anush Martirosyan; Sona Margaryan; Aida Avetisyan; Zaruhi Khachatryan; Gayane Manukyan (PLoS ONE, 2025)
The short lifespan of polymorphonuclear neutrophils (PMNs) in vitro poses challenges, as their limited viability restricts functional assays and experimental manipulations. The HL-60 cell line serves as a valuable model for neutrophil-like differentiation, yet the functional relevance of ATRA- and DMSO-induced differentiation remains incompletely understood. In the present study, we aimed to characterize the differentiation potential of all-trans retinoic acid (ATRA) and dimethyl sulfoxide (DMSO) on HL-60 cells and compare their functionality with primary PMNs. Besides that, we performed profound immunophenotypes of the cells with multicolor cytometry, and evaluated their antitumor capabilities. Our findings indicate that both differentiation conditions yield cells resembling immature neutrophils, exhibiting promyelocyte-like morphology, lacking key maturity markers. However, ATRA-differentiated cells exhibit a more mature phenotype, with higher expression of C/EBPα and reduced proliferation rates, indicating advanced differentiation. Functionally, ATRA-dHL-60 cells displayed limited immune responses, showing minimal phagocytic activity, low ROS production, and a reduced response to LPS. In contrast, DMSO-dHL-60 cells, despite their less mature phenotype, showed enhanced NET formation, and tumor-promoting potential. Additionally, DMSO-dHL-60 cells demonstrated superior adhesion and migration abilities, likely due to increased expression of CD18 and CD31. Overall, different differentiation conditions shape the functional specialization of HL-60 cells, with ATRA promoting a more neutrophil-like maturation and moderate activation, while DMSO results in a more immature phenotype with enhanced NET formation. These distinct properties suggest that ATRA-dHL-60 cells may better model neutrophils in chronic inflammation, whereas DMSO-dHL-60 cells could be more suitable for studying NETosis-driven autoimmune, thrombotic disorders and cancer.